Unjuk Rasa Anarkis Saat Pelaksanaan Hak Atas Kebebasan Berpendapat - Siti Zubaidah; Kamsilaniah Kamsilaniah; M. Amil Shadiq; Abd. Haris Hamid; Fitriani Fitriani (SIGn Jurnal Hukum, 2022)
This research analyzed anarchist demonstrations by undergraduate students while expressing opinions in public. The study used normative and empirical research methods, including direct interviews and a literature review of legal materials. Results showed that these anarchist demonstrations occur in Indonesia and other countries. Several factors motivated the protest masses to participate in anarchist demonstrations: the Government’s failure to respond to their aspirations, the presence of certain provocateurs, and the Police’s inability to control the protest masses. Meanwhile, the Police take measures to prevent anarchist demonstrations: the field coordinators of the protest masses must inform before the demonstration, urge the protest masses for a peaceful demonstration and respect citizens’ rights around the demonstration location, and disband anarchist demonstrations. In addressing the root causes of anarchist demonstrations, it is recommended that the Government and members of Parliament take proactive measures, such as responding to the protest masses’ aspirations. At the same time, the Police and undergraduate students in demonstration locations should continue enforcing the provisions under applicable legislation. These efforts can maintain peace and order for undergraduate students during demonstrations while protecting the rights of citizens to express opinions in public.